Baseline FDG PET CT for Evaluation of Primary Extranodal Lymphoma: A Multi Center Cross Sectional Study (Bangladesh Journal of Nuclear Medicine, 2026)
Extranodal lymphoma comprises 20-30% of all lymphomas, and diagnosis at presentation is a challenge due to the wide range of presentations. To see the pattern of disease involvement at presentation as well as to assess the role of 18F-FDG PET-CT in diagnosing extranodal lymphoma. This cross-sectional study was conducted in the Institute of Nuclear Medicine and Allied Sciences, Dhaka, along with one well-equipped private PET-CT center from January 2021 to December 2023 among 98 patients having pathologically and immunohistochemistry-proven primary extranodal lymphoma without a history of prior treatment. Maximum patients (22) were in the 50–59-year age group with male predominance (56%). 96% were non-Hodgkin’s lymphoma histopathologically. Among the non-Hodgkin’s group, 29% of patients presented with gastrointestinal involvement and 10% with skeletal lesions. 8% showed orbital primary, and another 8% had tonsil as the primary site of involvement. The rest of the primary sites included thyroid (6%), bone marrow (5%), thymus (2%), brain (2%), nasopharynx (5%), tongue (4%), other head and neck regions (3%), vagina (2%), ovary (2%), spleen (5%), liver (1%), muscular (2%), and cutaneous (2%). Hepatosplenomegaly was present in 32% of patients, while the rest did not have any organomegaly. No FDG-avid lymph nodes were found in 76% of the patients. The SUV max of FDG-avid lesions ranged from 5 to 40. 52% of FDG-avid lesions had an SUV max from 11 to 20. FDG PET-CT enables accurate detection of involvement of unusual organs with lymphomatous infiltration even without morphologic change.Bangladesh J. Nuclear Med. 29(1): 58-63, 2026